The social state progress in foreign countries - V K Filatov (RUDN Journal of Law, 2013)
This article puts forward and substantiates the thesis that the social state is the answer to the challenges of history with the end of the 19th century up to our days, which allowed the basic foreign countries in periods of crisis not only to overcome the socio-economic and political problems, but also to move to a qualitatively new level of development.